Error analysis and uncertainty estimation for a millimeter-wave phase-shift measurement system at 325 GHz. (January 2015) - Wu, T.Y.; Lu, Y.L.
Highlights: Error analysis for a millimeter-wave phase-shift measurement system at 325 GHz are presented. The measurement errors due to noise, drift, mismatch and leakage are evaluated. We also estimate the errors due to inductive voltage divider and repeatability. The expanded uncertainties in phase-shift measurement are estimated. Phase-shift measurement uncertainties for a 0–60 dB attenuator are 0.57–1.3° at 325 GHz. Abstract: Error analysis and uncertainty estimation for a millimeter-wave phase-shift measurement system at 325 GHz are presented. The measurement errors due to inductive voltage divider, receiver noise, phase drift, mismatch at test ports, gauge-block attenuator, leakage and repeatability have been identified and evaluated. The standard uncertainty of these error components have been estimated and combined to obtain the expanded uncertainty in phase-shift measurement. The differential phase-shift measurement uncertainty for a 0–60 dB WR-03 rotary vane attenuator is estimated to be 0.57–1.3° at 325 GHz.